Cervical facet force analysis after disc replacement versus fusion. (May 2017) - Patel, Vikas V.; Wuthrich, Zachary R.; McGilvray, Kirk C.; Lafleur, Matthew C.; Lindley, Emily M.; Sun, Derrick; Puttlitz, Christian M.
Abstract: Background: Cervical total disc replacement was developed to preserve motion and reduce adjacent-level degeneration relative to fusion, yet concerns remain that total disc replacement will lead to altered facet joint loading and long-term facet joint arthrosis. This study is intended to evaluate changes in facet contact force, pressure and surface area at the treated and superior adjacent levels before and after discectomy, disc replacement, and fusion. Methods: Ten fresh-frozen human cadaveric cervical spines were potted from C2 to C7 with pressure sensors placed into the facet joints of C3–C4 and C4–C5 via slits in the facet capsules. Moments were applied to the specimens to produce axial rotation, lateral bending and extension. Facet contact force and pressure were measured at both levels for intact, discectomy at C4–C5, disc replacement with ProDisc-C (Synthes Spine, West Chester, Pennsylvania, USA) at C4–C5, and anterior discectomy and fusion with Cervical Spine Locking Plate (Synthes Spine, West Chester, Pennsylvania, USA) at C4–C5. Facet contact area was calculated from the force and pressure measurements. An analysis of variance was used to determine significant differences with P -values < 0.05 indicating significance. Findings: Facet contact force was elevated at the treated level under extension following both discectomy and disc replacement, while facet contact pressure and area were relatively unchanged. Facet contact force and area were decreased at the treated level following fusion for all three loading conditions. Interpretation: Total disc replacement preserved facet contact force for all scenarios except extension at the treated level, highlighting the importance of the anterior disco-ligamentous complex. This could promote treated-level facet joint disease. Highlights: Measured facet contact forces directly via slit incisions in facet capsule ligaments Analyzed treated and superior adjacent-level cervical facet joints Compared intact, discectomy, total disc replacement, fusion treatments Increased facet force at treated level under extension following disc replacement Decreased facet contact area at adjacent level following disc replacement and fusion